Prevalence of Nonalcoholic Steatohepatitis and Associated Fibrosis Stages Among US Adults Using Imaging-Based vs Biomarker-Based Noninvasive Tests - Jesse Fishman; Tom O'Connell; Christina M. Parrinello; Jonathan J. Woolley; Eric Bercaw; Michael R. Charlton (Journal of Health Economics and Outcomes Research)
**Introduction:** Nonalcoholic fatty liver disease (NAFLD) is believed to be the most common chronic liver disease worldwide. Therapies are under development for nonalcoholic steatohepatitis (NASH), the progressive form of NAFLD, such that the prevalence of NASH with liver fibrosis, which is likely to require treatment, may be of interest to healthcare decision makers. Noninvasive tests are used in initial screening for NASH, as well as in observational studies of NASH prevalence. However, existing evidence does not address how estimated prevalence varies with different noninvasive tests. This analysis estimated the prevalence of NASH among US adults and assessed variation with different noninvasive tests.